Multiple system atrophy variant with severe hippocampal pathology. (13th July 2021) - Ando, Takashi; Riku, Yuichi; Akagi, Akio; Miyahara, Hiroaki; Hirano, Mitsuaki; Ikeda, Toshimasa; Yabata, Hiroyuki; Koizumi, Ryuichi; Oba, Chisato; Morozumi, Saori; Yasui, Keizo; Goto, Atsuko; et al.
Abstract: The striatonigral and olivopontocerebellar systems are known to be vulnerable in multiple system atrophy (MSA), showing neuronal loss, astrogliosis, and alpha‐synuclein‐immunoreactive inclusions. MSA patients who displayed abundant neuronal cytoplasmic inclusions (NCIs) in the regions other than the striatonigral or olivopontocerebellar system have occasionally been diagnosed with variants of MSA. In this study, we report clinical and pathologic findings of MSA patients characterized by prominent pathologic involvement of the hippocampus. We assessed 146 consecutively autopsied MSA patients. Semi‐quantitative analysis of anti‐alpha‐synuclein immunohistochemistry revealed that 12 of 146 patients (8.2%) had severe NCIs in two or more of the following areas: the hippocampal granule cells, cornu ammonis areas, parahippocampal gyrus, and amygdala. In contrast, the remaining 134 patients did not show severe NCIs in any of these regions. Patients with severe hippocampal involvement showed a higher representation of women (nine women/three men; Fisher's exact test, p = 0.0324), longer disease duration (13.1 ± 5.9 years; Mann–Whitney U‐test, p = 0.000157), higher prevalence of cognitive impairment (four patients; Fisher's exact test, p = 0.0222), and lower brain weight (1070.3 ± 168.6 g; Mann–Whitney U‐test, p = 0.00911) than other patients. The hippocampal granule cells and cornu ammonis area 1/subiculum almost always showed severe NCIs. The NCIs appeared to be ring‐shaped or neurofibrillary tangle‐like, fibrous configurations. Three of 12 patients also had dense, round‐shaped NCIs that were morphologically similar to pick bodies. The patients with Pick body‐like inclusions showed more severe atrophy of the medial temporal lobes and broader spreading of NCIs than those without. Immunohistochemistry for hyperphosphorylated tau and phosphorylated TDP‐43 revealed minimal aggregations in the hippocampus of the hippocampal MSA patients. Our observations suggest a pathological variant of MSA that is characterized by severe involvement of hippocampal neurons. This phenotype may reinforce the importance of neuronal alpha‐synucleinopathy in the pathogenesis of MSA. Abstract : This study describes a clinicopathological phenotype of the hippocampal multiple system atrophy (MSA) characterized by abundant alpha‐synuclein‐immunopositive neuronal cytoplasmic inclusions and neuronal loss in the hippocampus with concomitant cognitive impairment in the patients. The phenotype may be a pathological variant of MSA and reinforces the importance of neuronal alpha‐synucleinopathy in the pathogenesis of MSA.